DYSFUNCTIONAL AUDIT BEHAVIOR DALAM PERSPEKTIF THEORY OF ATTITUDE CHANGES (Study Pada Auditor BPKP DKI Jakarta) - Djaddang, Syahril; Ikhsan Husaeni, Muhammad; Fujianti, Lailah (SEKOLAH PASCASARJANA PRESS, 2016)
This research is aimed to get an empirical proof of the effect locus of control and auditor’s performance have in regards to dysfunctional audit behavior with time budget pressure as moderator. The research was held at Badan Pengawasan Keuangan dan Pembangunan (BPKP) DKI Jakarta located in East Jakarta. The sampling method used in this research is snowballing sampling. This research is a Moderated Regression Analysis (MRA). This research shows that locus of control has no effect on dysfunctional audit behavior because of the variety of auditor’s culture existing in BPKP DKI Jakarta, time budget pressure strengthens the effect of locus of control on dysfunctional audit behavior because time budget pressure motivates self-control in auditors employed by BPKP DKI Jakarta, auditor performance is negatively significant in relations to dysfunctional audit behavior because they work professionally, and time budget pressure weakens the effect of auditor performance on dysfunctional audit behavior because the our community is trenched in the Eastern tradition of not being able to handle pressures.